PENGARUH STRATEGI POW + C- SPACE TERHADAPKETERAMPILAN MENULIS NARASI SISWA KELAS VDI SDN 102 PEKANBARU - Otang Kurniaman; Adian Syahputra Nasution; Zariul Antosa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by students’ poor writing skills in learning writing skills. This was due to several problems experienced by students, such as students’ lack of knowledge of elements in writing, sentence composing, correct use of words and punctuations, and having difficulty expressing their ideas in a narrative essay. This study aimed to determine the differences and improvements in the pretest and post-test by using the POW + C-SPACE strategy on the narrative writing skills of grade V students of SDN 102 Pekanbaru. This type of research was an experiment with a pre-experimental design method. The sample in this study amounted to 30 students. The data were collected through tests. The research instrument was a test to assess students’ narrative writing skills in Bahasa Indonesia. Based on the research results, a significant increase was obtained between the average class score on the pre-test (pretest), 60.36, and the average class score on the final (post-test) test, 79.9. In the gain index, there was a difference with an average increase of 0.51, namely the medium category.